The dynamics of illicit drugs production: future sources and threats - Morrison, Shona (Crime, law and social change, 1997)
This paper examines the opportunities for illicit drugs production which arise out of the economic, political and social conditions of some countries. These drivers can help us to understand the geographical pattern of global drugs sources and assist in the process of identifying those parts of the world in which new production opportunities are arising. It was found that there is not a homogenous set of risks which contributes to drugs production. Instead, the particular contexts which are conductive to drug production activities varies for different drug types. This has influenced the different patterns of drugs production for highly refined, organic drugs, such as cocaine and heroin, compared to synthetic drugs. The nature of developments which could trigger new areas of drug production are discussed.